2014
DOI: 10.1159/000365570
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Testicular Adrenal Rest Tumours during Adolescence in Congenital Adrenal Hyperplasia

Abstract: Testicular adrenal rest tumours (TART) are one of the most important causes of infertility in adult male patients with congenital adrenal hyperplasia (CAH). These benign tumours are already detected in children, but screening of TART is not routinely performed. Objective: To define retrospectively the prevalence of TART in 41 paediatric male CAH patients aged 0-19 years regularly followed by high-frequency (Fcentral 12-MHz) ultrasound techniques. Results: Above the age of 10 years, there was a clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 40 publications
(64 reference statements)
5
37
2
Order By: Relevance
“…Compared to other authors [8, 27], however, the prevalence in this study was low. Kang et al [27] found TART in 64.6% of 48 patients aged 10.6–27.1 years, who had 82.4% of 17-OHP dosages above 10 ng/mL; this percentage was higher than that found in this study in the 6 years before ultrasonography (41.7%).…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Compared to other authors [8, 27], however, the prevalence in this study was low. Kang et al [27] found TART in 64.6% of 48 patients aged 10.6–27.1 years, who had 82.4% of 17-OHP dosages above 10 ng/mL; this percentage was higher than that found in this study in the 6 years before ultrasonography (41.7%).…”
Section: Discussioncontrasting
confidence: 98%
“…We also believe that the prevalence among pubertal patients in this study (18.5%) is lower than that of Claahsen-van der Grinten et al [8] probably because these patients had a better control: 10 of 38 patients (26.3%) had high Andro levels in the 2 years prior to ultrasonography, while Claahsen-van der Grinten et al reported that 19 of the 41 patients (46.3%) had Andro levels above the normal limit.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations